2021
DOI: 10.1080/10888438.2021.1983820
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Precursors of Reading: A Cross-Linguistic Perspective

Abstract: In this paper, we survey current evidence on cognitive precursors of reading in different orthographies by reviewing studies with a cross-linguistic research design. Graphic symbol knowledge, phonological awareness, morphological awareness, and rapid automatized naming were found to be associated with reading acquisition in all orthographies investigated. However, apart from rapid naming, this association is mostly interactive, meaning that young children develop their symbol knowledge, and phonological and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 83 publications
(100 reference statements)
5
49
0
4
Order By: Relevance
“…There have been some studies probing the first (e.g., Huettig & Mishra, 2014;Morais et al, 1986;Wolf, 2015) and the second (e.g., Georgiou et al, 2008;Landerl et al, 2021;Nag & Perfetti, 2014;Prakash et al, 1993;Rao et al, 2017;Winskel & Kim, 2021) question. These studies show enough evidence favoring the view that there are certain differences between literate and illiterate minds/brains in their functional organization.…”
mentioning
confidence: 99%
“…There have been some studies probing the first (e.g., Huettig & Mishra, 2014;Morais et al, 1986;Wolf, 2015) and the second (e.g., Georgiou et al, 2008;Landerl et al, 2021;Nag & Perfetti, 2014;Prakash et al, 1993;Rao et al, 2017;Winskel & Kim, 2021) question. These studies show enough evidence favoring the view that there are certain differences between literate and illiterate minds/brains in their functional organization.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to clarify the role of phonological processing in Chinese reading acquisition and the corresponding neuro‐cognitive mechanisms. The increasing number of studies support the importance of phonological processing in Chinese reading development (Chow et al., 2005; Chung & Bidelman, 2021; Landerl et al., 2021; Liet al., 2012; Shu et al., 2008; Siok & Fletcher, 2001; Wang & Bi, 2021). For example, researchers found that children with dyslexia manifested deficits in speech perception (e.g., lexical tones were less categorically perceived) (Cheung et al., 2009) and showed abnormal neural responses (Zhang et al., 2012).…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting that while the neural signature for fluent reading is universal (Rueckl et al., 2015), linguistic characteristics, such as orthographic depth, can modulate the precise manifestations of particular components in the reading system (Richlan, 2014). Thus, testing a hypothesis developed in specific languages with other languages characterized by different linguistic features is necessary for clarifying its universality (Landerl et al., 2021). In terms of the speech‐reading relationship, letters directly code speech sounds in alphabetic languages, known as grapheme‐phoneme correspondence (GPC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors associated with visual processing such as visual memory span at kindergarten age ( 29 ) have been researched experimentally, but to our knowledge, there is still a lack of established test paradigms shown to be feasible within school-based screenings. Related to linguistically based predictors in alphabetic languages, letter knowledge, phonological awareness, and Rapid Automatized Naming-speed (RAN) have been demonstrated as robust predictors of word reading even across different orthographies and a number of reliable and practicable test paradigms have been developed ( 30 ). These factors, often summarized as phonological information processing ( 31 , 32 ), are frequently supplemented by phonological working memory ( 33 ).…”
Section: Introductionmentioning
confidence: 99%